HOW TO MAKE ISLAMIC LAW AS THE STATE LEGAL POLICY OF INDONESIA: Constitutional and Sociological Arguments - Hapsin, Abu (Al-Ahkam, 2017)
This article aims to answer some questions: what is the meaning of â€œequal rightâ€ and â€œreligious freedomâ€ written in the text of UUD 45? How if, in the name of religious freedom, other peopleâ€™s rights are offended? how if, in implementing Islamic law, others peopleâ€™s rights are offended? Indonesian Constitution (UUD 45) gives freedom to every follower of a given religion to concretize his religious convictions in public life provided that, in doing so, the fundamental right of others are not offended. The UUD 45 also gives freedom to every citizen to make his religious convictions or religious teachings become a state legal policy as long as he or she follows the procedural constitution written in the UUD 45. However, after becoming state legal policy, Islamic law can no longer be claimed â€œIslamic Lawâ€, because itâ€™s now provided for answering the partial question of life, namely how to administer the state. From a sociological point of view, in order that the process of legislation runs smoothly, Islamic Law should first be transformed into living norms. Hence, it will be easier for the society to abide the law which originated from living norms. Since the function of law in maintaining public peace and order depends, for its effectiveness, on the actual social norms of the community, social acceptance is of great importance. Two ways of resolution will be discussed in this article, these are democratic resolution and transforming Islamic Law into social norms.[]Artikel ini bertujuan untuk menjawab beberapa pertanyaan, apa arti "hak yang sama" dan "kebebasan beragama" yang tertulis dalam teks UUD 45? Bagaimana jika atas nama keÂbebasan beragama bersinggungan dengan hak orang lain? Bagaimana pula jika dalam menerapkan hukum Islam mengganggu ataupun mengabaikan hak orang lain? UUD 1945 memberikan kebebasan kepada setiap penganut agama untuk mengekspresikan keÂyakinan agamanya dalam kehidupan publik dengan cacatan tidak mengganggu dan mengabaikan hak orang lain. UUD 1945 juga memberikan kebebasan kepada setiap warga negara untuk membuat keyakinan agama atau ajaran agamanya menjadi keÂbijakan hukum negara selama tetap mengikuti prosedur yang tertulis dalam UUD 1945. Namun, setelah menjadi kebijakan hukum negara, hukum Islam tidak dapat lagi diklaim sebagai "Hukum Islam", karena hukum tersebut telah dibuat dalam rangka memÂberikan solusi terhadap berbagai macam permasalahan dalam kehidupan, lebih tepatnya hukum terÂsebut telah menjadi pengatur sebuah Negara. Dari sudut pandang sosiologis, agar proses perundang-undangan berjalan lancar, Hukum Islam pertama-tama harus diubah menjadi norma hidup sehingga akan lebih mudah bagi masyarakat untuk mematuhi hukum yang berawal dari norma hidup. Karenanya hukum berfungsi dalam menjaga ketertiban publik, dan ini bergantung pada norma sosial yang berlaku pada masyarakat, sehingga akan mudah diterima oleh masyarakat. Dua tawaran solusi akan dibahas dalam artikel ini, yaitu: resolusi demokratis dan mengÂubah Hukum Islam menjadi norma sosial.